A novel autolysis system controlled by magnesium and its application to poly (3-hydroxypropionate) production in engineered Escherichia coli. Issue 5 (3rd September 2017) - Tamekou Lacmata, Stephen; Yao, Lan; Xian, Mo; Liu, Hui; Kuiate, Jules-Roger; Liu, Huizhou; Feng, Xinjun; Zhao, Guang
ABSTRACT: The release of intracellular products, especially polyhydroxyalkanoates, is still a great challenge in industry. To solve this bottleneck, a novel autolysis system strictly controlled with magnesium was constructed and applied to poly(3-hydroxypropionate) production in engineered Escherichia coli . The autolysis system was constructed by inserting the 5′untranslated region (5′UTR) behind promoter P mgtA with lysis genes ( S, R, and Rz, from E. coli ) overexpressed. The autolysis system functioned well (lysis efficiency of more than 90%) in the P3HP producer with double plasmids containing lysis genes and P3HP biosynthesis genes, whereas the P3HP production was reduced due to plasmid losses. After the autolysis genes and P3HP biosynthesis genes were integrated into one plasmid, the P3HP content of 72.7% (2.4 times of the control) and the plasmid stability of 79.8 ± 3.1% were achieved in strain Q2646 with promoter P mgtA- UTR. However, the strain Q2647 with promoter P mgtA could not accumulate P3HP because of rapid cell lysis. The novel autolysis system activated in Mg 2+ -depleted conditions proves to be feasible for polyhydroxyalkanoates production, which may have great application potential for other intracellular products.